Determinants of High School Students’ Economic Behavior - Nur Fajri Insan Islami; Komm Pechinthorn (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: Students’economic behavior reflects how they make decisions in the economic field. Observations show that some 10th-grade students at State Senior High School 1 Menganti, Gresik, Indonesia, stikk exhibit inappropriate economic behavior due to a lack of economic literacy, especially in understanding the concept of opportunity cost. This study aims to analyze the influence of teacher competence on student economic behavior. Method: the study used a quantitative approach and correlational research with 199 tenth-grade students at State Senior High School 1 Menganti as the sample. The data were collected via questionnaires and analyzed using SEM-PLS in SmartPLS. Results: the study indicates that teacher competence has a significant positive effect on economic behavior. The results of the study indicate the importance of teacher competence in shaping student economic behavior. Novelty: this research has the potential to be innovative, focusing on developing research that has not been widely discussed in existing literature, which has an impact on a person’s economic behavior.